The Diagnostic and Therapeutic Value of Multimarker Analysis in Heart Failure. An Approach to Biomarker-Targeted Therapy - Topf, Albert; Mirna, Moritz; Ohnewein, Bernhard; Jirak, Peter; Kopp, Kristen; Fejzic, Dzeneta; Haslinger, Michael; Motloch, Lukas J.; Hoppe, Uta C.; Berezin, Alexander; Lichtenauer, Michael (Frontiers in Cardiovascular Medicine, 2020)
Background: Heart failure is a pathophysiological state, which is still associated with high morbidity and mortality despite established therapies. Diverse well-known biomarkers fail to assess the variety of individual pathophysiology in the context of heart failure. Methods: An analysis of prospective, multimarker-specific therapeutic approaches to heart failure based on studies in current literature was performed. A total of 159 screened publications in the field of biomarkers in heart failure were hand-selected and found to be eligible for this study by a team of experts. Results: Established biomarkers of the inflammatory axis, matrix remodeling, fibrosis and oxidative stress axis, as well as potential therapeutic interventions were investigated. Interaction with end organs, such as cardio-hepatic, cardio-renal and cardio-gastrointestinal interactions show the complexity of the syndrome and could be of further therapeutic value. MicroRNAs are involved in a wide variety of physiologic and pathophysiologic processes in heart failure and could be useful in diagnostic as well as therapeutic setting. Conclusion: Based on our analysis by a biomarker-driven approach in heart failure therapy, patients could be treated more specifically in long term with a consideration of different aspects of heart failure. New studies evaluating a multimarker – based therapeutic approach could lead in a decrease in the morbidity and mortality of heart failure patients.